ANALISIS INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN DI KANTOR PERUSAHAAN DAERAH AIR MINUM KABUPATEN ENDE - Rafael Octavianus Byre (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Abstrac : The purpose of this study was to determine the satisfaction index of the people of Ende city in services at the PDAM Ende Office. The approaches in this study are qualitative and quantitative approaches. The population in this was 14.624 people. The sample sampling technique used in this study was accidental sampling. The sample in this study was 99 respondents. The types of data used in this study are qualitative data and quantitative data. The data sources used in this study are primary data and secondary data. The data collection techniques used in this study were questionnaires, documentation, and interviews. The data analysis technique carried out in this study is data processing. The result of this study is that average value of the public statisfaction index in PDAM Tirta Kelimutu Ende office services is 2,975 and is categorized as good. Meanwhile, the IKM confection value from services at the PDAM Tirta Kelimutu Office, Ende Regency, was 74,375. The shows that overall the IKM indicator can akready be met because its value falls into the good category.